2013
DOI: 10.1021/ol4000873
|View full text |Cite
|
Sign up to set email alerts
|

Hg(II)-Mediated Intramolecular Cyclization Reaction in Aqueous Media and Its Application as Hg(II) Selective Indicator

Abstract: The Hg(II)-specific intramolecular cyclization reaction of ethynyl phenols was carried out for the first time in semiaqueous media at ambient temperature. The reaction unit (ethynyl phenol) was coupled with a malononitrile derivative (signal unit), which afforded the chromogenic Hg(II) indicator 7. The reaction of the chromogenic Hg(II) indicator 7 was further optimized in DMSO/water (3:7, v/v) (10 mM PBS buffer, pH = 7.0). Compound 7 displays a color change from blue to pale yellow in the presence of Hg(II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…These similar values obtained from two different titration methods supported the validity of the constants. In addition, the limit of detection (LOD) for Cd 2+ was calculated using the 3σ method (σ = 1.039, m = 1.97 × 10 7 M −1 ) [7] and found to be 158 nM (Figure S4 in the ESI). To further investigate the binding mode of Cd 2+ with 2b, 1 H NMR titration of 2b (2.0 mM) was performed with Cd 2+ in CD 3 CN (Figure S9 in the ESI).…”
Section: Cation-binding Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These similar values obtained from two different titration methods supported the validity of the constants. In addition, the limit of detection (LOD) for Cd 2+ was calculated using the 3σ method (σ = 1.039, m = 1.97 × 10 7 M −1 ) [7] and found to be 158 nM (Figure S4 in the ESI). To further investigate the binding mode of Cd 2+ with 2b, 1 H NMR titration of 2b (2.0 mM) was performed with Cd 2+ in CD 3 CN (Figure S9 in the ESI).…”
Section: Cation-binding Studiesmentioning
confidence: 99%
“…Recently, our group recognized the fluorescent dye properties of some tolan derivatives without the help of conjugation with other types of dyes. These tolans can function as switches [3,4], sensors [5][6][7], and β-turn mimics [8] depending on various installed motifs. They also exhibit a range of fluorescence quantum yields.…”
Section: Introductionmentioning
confidence: 99%
“…8 The use of a malononitrile derivative as an electronwithdrawing group has led to the development of a Hg(II) selective indicator that displays a color change from blue to pale yellow.…”
Section: Abstracts (A) Preparation Of Asymmetrical Nn'-disubstitutedmentioning
confidence: 99%
“…Besides novel mercuration reactions with organic substrates, [3][4][5][6][7] HgCl 2 has been extensively used in a variety of cyclization reactions, forming both carbocycles and heterocycles. [8][9][10] Its use as inorganic thiophile has led to the formation of several new products from organosulfur reactants, especially thiocarbonyl compounds. [11][12][13][14][15][16] Finally, the synthesis of mercury(II) alkynyls, mainly from HgCl 2 , and their use as building blocks for supramolecular structures has been reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…In many studies, it can be seen that kinds of chemosensors have been developed as fluorescent sensor for detecting Hg 2+ ions. For example, Atta et al reported a specific intramolecular cyclization of Hg 2+ of reaction of ethynyl phenols to act as an Hg 2+ ions indicator. Chen et al reported a new fluorescent chemosensor for double signaling behaviors for Hg 2+ ions and Ag + ions in aqueous solution, which was based on the chromophore of naphthalimide and thioether‐rich crown as receptor.…”
Section: Introductionmentioning
confidence: 99%